A method for preparing non-aluminum deoxidized industrial pure iron
By using low-manganese, low-sulfur slag steel and silicon + lime powder combined deoxidation technology, the problem of manganese content and oxygen content control of molten steel is solved, and high-quality preparation of industrial pure iron is achieved.
Patent Information
- Application Number
- CN202310140974.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-02-21
AI Technical Summary
The prior art is difficult to effectively control the manganese content and oxygen content of molten steel, resulting in complex smelting process and difficult to meet quality requirements.
The internally produced low-manganese and low-sulfur slag steel are used as special scrap steel, and the combination of silicon + lime powder is used to deoxygenate during the RH deoxygenation process to control the alkalinity of the slag to achieve deep deoxygenation.
Through this method, the difficulty of controlling manganese content is reduced, and the deep deoxygenation of low-silicon steel is achieved. The oxygen content of the molten steel can be controlled within 20ppm, meeting the quality requirements of industrial pure iron.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallurgy, and particularly relates to a method for preparing non-aluminum deoxidized industrial pure iron. Background Art
[0002] Industrial pure iron is a metal material with a very low carbon content. Its chemical composition is mainly iron, and the lower the other alloying elements, the better. The room temperature structure of industrial pure iron is mainly ferrite, and it has the characteristics of soft texture, high toughness, good ductility, and excellent electromagnetic properties. Al and Al2O3 inclusions in the raw pure iron are likely to cause nozzle blockage and belt breakage in the subsequent preparation process, so aluminum deoxidation cannot be used in the steelmaking process; at the same time, the manganese content of industrial pure iron is extremely low, and the silicon content is required not to be too high, and the oxygen content control in the smelting process is extremely difficult. Controlling the manganese and oxygen content in molten steel is a difficulty in smelting this type of steel.
[0003] In order to control the manganese content of molten steel, low-manganese iron water and low-manganese scrap steel are generally required. Low-manganese iron water can be supplied through internal coordination of the company, but the scrap steel collected on the market or recycled by conventional methods within the factory has a relatively high manganese content, and low-manganese scrap steel is difficult to obtain. The manganese content of scrap steel purchased on the market is currently very unstable, ranging from 0.1 to 1.5%, with an average of about 0.35%, and low-manganese scrap steel and high-manganese scrap steel are mixed together and difficult to distinguish; using this type of scrap steel combined with the converter single slag method for smelting, the manganese content at the converter end is difficult to meet the requirements.
[0004] Patent CN115261564 A discloses non-aluminum deoxidized raw material pure iron for amorphous soft magnetic thin strip and its preparation method. The obtained industrial pure iron has the following components in mass percentage: [C]≤0.005%, [Si]≤1.0%, [Mn]≤0.06%, [P]≤0.015%, [S]≤0.010%, [Al]≤0.005%, [Ti]≤0.0040%, [N]≤0.0040%, T[O]≤0.0070%, and the rest is Fe and unavoidable impurities, and the Si content is required to be ≤1.0%, and T[O] is ≤0.0070%. Desulfurized and demanganized iron water is used, no scrap steel is added, and the manganese content of the converter end point is controlled by the converter double slag method; at the same time, in order to control the oxygen content of the molten steel without aluminum deoxidation, the silicon content in the molten steel is above 0.65%. Summary of the invention
[0005] The present invention provides a method for preparing non-aluminum deoxidized industrial pure iron, wherein the industrial pure iron has the following components by weight percentage: [C]≤0.01%, [Si]≤0.50%, [Mn]≤0.05%, [P]≤0.02%, [S]≤0.010%, [Ti]≤0.005%, [Al]≤0.005%, [O]≤0.002%, and the rest is Fe. The production process of the present invention adopts internally produced low-manganese and low-sulfur slag steel as special scrap steel, which can reduce the difficulty of controlling manganese content; the RH deoxidation process adopts silicon + lime powder combined deoxidation, which can realize deep water deoxidation of low-silicon steel.
[0006] The process is as follows:
[0007] BOF smelting → LF refining → RH decarburization and deoxidation → continuous casting. The specific steps and process parameters are as follows:
[0008] Step 1, BOF smelting, converter smelting adopts the smelting method of molten iron + special scrap steel, the molten iron ratio is controlled at 70%~80%, the special scrap steel ratio is controlled at 20%~30%, and the single slag method is adopted; the terminal temperature is controlled at 1620~1650℃, and the terminal composition is controlled at [C]≤0.05%, [Mn]≤0.05%, [P]≤0.015%, [S]≤0.025%, [Ti]≤0.002%; no deoxidizer and alloy are added in the steelmaking process, only lime and fluorite are added, and the slide plate + slag plug double-speed operation is adopted.
[0009] Step 2, LF refining, after the molten steel reaches the refining stage, it is powered on to increase the temperature. After the refining treatment, the temperature of the molten steel is controlled at 1640-1670°C, and the composition of the molten steel is [C]≤0.05%, [Mn]≤0.05%, [P]≤0.015%, [S]≤0.025%, [O]0.04-0.09%.
[0010] Step 3, RH decarburization and deoxidation, the RH arrival temperature is controlled at 1630-1660°C, and the molten steel is subjected to cyclic decarburization treatment after reaching the RH, using argon as the lifting gas, and the vacuum degree is controlled at 67-1000Pa. After decarburization treatment, the carbon content of the molten steel is controlled to be ≤0.002%, and the oxygen content of the molten steel is 0.02%-0.06%; then low-titanium, low-aluminum ferrosilicon and lime are added for deoxidation treatment; after breaking the air, a low-carbon ladle covering agent with a carbon content of ≤2% is added.
[0011] Step 4: continuous casting. The continuous casting process uses 160mm×160mm cross-section production. The continuous casting tundish adopts an integral smear plug rod tundish. The tundish is baked to 1050-1150℃. The superheat of the first furnace is controlled at 40-50℃, the superheat of the continuous casting furnace is controlled at 25-35℃, and the pulling speed is controlled at 2.1-2.5m / min. The crystallizer adopts electromagnetic stirring and non-sinusoidal vibration mode. The secondary cooling adopts mist cooling and weak cooling water distribution. The continuous casting process uses a low-carbon tundish covering agent with a carbon content of ≤2% and an ultra-low carbon protective slag with a carbon content of ≤8%.
[0012] Furthermore, as a preferred embodiment, in step one, the converter adopts a single slag method for smelting, the manganese content of the molten iron is ≤0.30%, and the sulfur content is ≤0.03%. The slag steel recovered from the converter smelting of low-sulfur steel grades (such as cord steel) is used as special scrap steel, and its composition is [C] ≤0.15%, [Mn] ≤0.10%, [P] ≤0.04%, [S] ≤0.025%, and [Ti] ≤0.005%.
[0013] Furthermore, preferably, in step one, the oxygen content of the final molten steel of the converter is controlled at 0.05% to 0.10%, the final slag basicity is controlled at 3.0 to 3.5, and the slag FeO is controlled at 15% to 25%.
[0014] Furthermore, preferably, in step 1, the amount of lime added is 3-6 kg / t, and the amount of fluorite added is 1-3 kg / t.
[0015] Furthermore, as a preference, in step 3, the argon flow rate of the circulating decarburization is 100-150 Nm 3 / h, and the cycle time is controlled at 3 to 8 minutes.
[0016] Furthermore, preferably, in step three, the amount of low-titanium and low-aluminum ferrosilicon added during deoxidation treatment is 3.0-6.5 kg / t, the amount of lime added is 2.5-4.5 kg / t, the silicon content of the molten steel after deoxidation treatment is controlled at 0.15%-0.45%, the sulfur content is controlled at ≤0.01%, and the slag basicity is >3.0.
[0017] Furthermore, preferably, in step three, the composition of the low-titanium and low-aluminum ferrosilicon is [Si]: 70-80%, [Al]≤0.03%, [Ti]≤0.02%, [P]≤0.02%, [S]≤0.010%, and the rest is iron.
[0018] Furthermore, preferably, in step three, the oxygen content of the molten steel after deoxidation treatment is ≤0.002%.
[0019] Furthermore, preferably, in step 4, the crystallizer electromagnetic stirring current is 120-180A, and the frequency is 2.2-2.8Hz; the crystallizer amplitude is controlled at -2.5-2.5mm, and the frequency is controlled at 130+40V opm.
[0020] The beneficial effects of the present invention are:
[0021] 1. The slag steel recovered from converter smelting is low-manganese scrap steel, which is more conducive to controlling the manganese content of molten steel. The converter does not need to use full molten iron and double slag method for smelting, which reduces the difficulty of converter smelting.
[0022] 2. RH adopts silicon deoxidation treatment and lime powder is sprayed. The deoxidation product SiO2 combines with CaO in the lime powder to generate stable 2CaO·SiO2, which promotes the deoxidation reaction. By controlling the slag basicity, deep deoxidation treatment under low silicon conditions (0.15%~0.30%) is achieved. The oxygen content of the molten steel after deoxidation can be controlled within 20ppm.
[0023] 3. The RH treatment process produces high-basicity, low-oxidizing slag, which meets the desulfurization conditions. After treatment, the sulfur content of molten steel can be stably controlled within 0.01%, and no additional molten iron desulfurization treatment is required. DETAILED DESCRIPTION
[0024] Example 1
[0025] 1. BOF smelting, using 115t molten iron + 30t special scrap steel as raw materials for smelting, the manganese content of the converter molten iron is 0.28%, the sulfur content is 0.023%, the carbon content of the special scrap steel is 0.06%, the manganese content is 0.06%, the phosphorus content is 0.015%, the sulfur content is 0.018%, and the titanium content is 0.002%; the single slag method is used for smelting; the components of the molten steel at the end of converter smelting are [C] 0.05%, [Mn] 0.05%, [P] 0.012%, [S] 0.021%, [Ti] 0.0010%, [O] 0.072%, the basicity of the converter slag at the end is 3.3, the FeO content of the slag is 18.0%, and the end temperature is 1640℃. 500kg lime + 200kg fluorite are added during the steel tapping process, and the double-blocking operation of slide plate + slag stopper is adopted.
[0026] 2. LF refining, the refining power is turned on to increase the temperature, and the outlet temperature is controlled at 1660℃. The composition of the molten steel is [C] 0.048%, [Mn] 0.048%, [P] 0.012%, [S] 0.021%, [Ti] 0.0010%, and [O] 0.070%.
[0027] 3. RH decarburization and deoxidation, temperature measurement and oxygen determination after RH arrives at the station. The temperature of molten steel is 1650℃, and the oxygen content of molten steel is 0.068%; it is circulated under a vacuum of 120Pa, and argon is used as the lifting gas with a flow rate of 120Nm 3 / h, and after 5 minutes of circulation, the sample was taken, and the composition of the molten steel was [C] 0.001%, [Mn] 0.047%, [P] 0.012%, [S] 0.020%, [Ti] 0.0010%, [O] 0.026%; at this time, 450kg of low-titanium and low-aluminum ferrosilicon and 350kg of lime were added, and the composition of low-titanium and low-aluminum ferrosilicon was [Si] 76%, [Al] 0.02%, [Ti] 0. 01%, [P] 0.015%, [S] 0.010%, and the rest is iron; after circulating for 5 minutes, the sample is taken, and the composition of the molten steel is [C] 0.001%, [Si] 0.21%, [Mn] 0.047%, [P] 0.012%, [S] 0.005%, [Ti] 0.0010%, [Al] 0.0016%, [O] 0.0015%; the slag basicity is 3.2. After deoxidation, continue to circulate for 5 minutes to end the vacuum, and add low-carbon ladle covering agent (carbon content ≤ 2%) on the surface of the molten steel.
[0028] 4. Continuous casting: The continuous casting process uses a 160mm×160mm cross-section for production. The continuous casting tundish uses an integral smear plug rod tundish, which is baked to 1130°C. This furnace is the first furnace to be poured, and the superheat is controlled at 45°C and the pulling speed is controlled at 2.2m / min. The crystallizer adopts electromagnetic stirring and non-sinusoidal vibration mode. The electromagnetic stirring current of the crystallizer is 150A and the frequency is 2.5Hz. The crystallizer amplitude is controlled at ±2.5mm and the frequency is controlled at 130+40Vopm. The secondary cooling adopts gas mist cooling and weak cooling water distribution. The continuous casting process uses a low-carbon tundish covering agent with a carbon content of ≤2% and an ultra-low carbon protective slag with a carbon content of ≤8%.
[0029] The composition of the finished steel is: [C] 0.002%, [Si] 0.21%, [Mn] 0.046%, [P] 0.012%, [S] 0.005%, [Ti] 0.0010%, [Al] 0.0015%, [O] 0.0013%, and the rest is iron.
[0030] Example 2
[0031] 1. BOF smelting, using 105t molten iron + 40t special scrap steel as raw materials for smelting, the manganese content of the converter molten iron is 0.25%, the sulfur content is 0.022%, the carbon content of the special scrap steel is 0.08%, the manganese content is 0.045%, the phosphorus content is 0.018%, the sulfur content is 0.020%, and the titanium content is 0.002%; the single slag method is used for smelting; the components of the molten steel at the end of converter smelting are [C] 0.04%, [Mn] 0.05%, [P] 0.011%, [S] 0.020%, [Ti] 0.0010%, [O] 0.088%, the basicity of the converter slag at the end is 3.5, the FeO content of the slag is 20.6%, and the end temperature is 1635℃. 500kg lime + 200kg fluorite are added during the steel tapping process, and the double-blocking operation of slide plate + slag stopper is adopted.
[0032] 2. LF refining, the refining power is turned on to increase the temperature, and the outlet temperature is controlled at 1670℃. The composition of the molten steel is [C] 0.038%, [Mn] 0.045%, [P] 0.012%, [S] 0.020%, [Ti] 0.0010%, and [O] 0.085%.
[0033] 3. RH decarburization and deoxidation, temperature measurement and oxygen determination after RH arrives at the station. The temperature of molten steel is 1660℃, and the oxygen content of molten steel is 0.085%; it is circulated under a vacuum of 200Pa, and argon is used as the lifting gas with a flow rate of 120Nm 3 / h, and after 5 minutes of circulation, the sample was taken, and the composition of the molten steel was [C] 0.001%, [Mn] 0.043%, [P] 0.012%, [S] 0.020%, [Ti] 0.0010%, [O] 0.036%; at this time, 520kg of low-titanium and low-aluminum ferrosilicon and 560kg of lime were added, and the composition of low-titanium and low-aluminum ferrosilicon was [Si] 76%, [Al] 0.02%, [Ti] 0. 01%, [P] 0.015%, [S] 0.010%, and the rest is iron; after circulating for 5 minutes, the sample is taken, and the composition of the molten steel is [C] 0.001%, [Si] 0.25%, [Mn] 0.043%, [P] 0.012%, [S] 0.004%, [Ti] 0.0010%, [Al] 0.0015%, [O] 0.0016%; the slag basicity is 4.2. After the deoxidation is completed, continue to circulate for 7 minutes before ending the vacuum, and add low-carbon ladle covering agent (carbon content ≤ 2%) on the surface of the molten steel.
[0034] 4. Continuous casting: The continuous casting process uses 160mm×160mm cross-section production. The continuous casting tundish adopts an integral smear plug rod tundish, and the tundish is baked to 1130℃. This furnace is a continuous casting furnace, the superheat is controlled at 30℃, and the pulling speed is controlled at 2.2m / min; the crystallizer adopts electromagnetic stirring and non-sinusoidal vibration mode, the crystallizer electromagnetic stirring current is 150A, and the frequency is 2.5Hz; the crystallizer amplitude is controlled at ±2.5mm, and the frequency is controlled at 130+40V opm; the secondary cooling adopts gas mist cooling and weak cooling water distribution; the continuous casting process uses a low-carbon tundish covering agent with a carbon content of ≤2% and an ultra-low carbon protective slag with a carbon content of ≤8%.
[0035] The composition of the finished steel is [C] 0.002%, [Si] 0.25%, [Mn] 0.042%, [P] 0.012%, [S] 0.004%, [Ti] 0.0010%, [Al] 0.0016%, [O] 0.0015%, and the rest is iron.
[0036] Example 3
[0037] 1. BOF smelting, using 110t molten iron + 35t special scrap steel as raw materials for smelting, the manganese content of the converter molten iron is 0.25%, the sulfur content is 0.019%, the carbon content of the special scrap steel is 0.08%, the manganese content is 0.07%, the phosphorus content is 0.021%, the sulfur content is 0.012%, and the titanium content is 0.002%; the single slag method is used for smelting; the components of the molten steel at the end of converter smelting are [C] 0.043%, [Mn] 0.046%, [P] 0.012%, [S] 0.019%, [Ti] 0.0010%, [O] 0.081%, the basicity of the converter slag at the end is 3.4, the FeO content of the slag is 20.2%, and the end temperature is 1645℃. 500kg lime + 200kg fluorite are added during the steel tapping process, and the double-blocking operation of slide plate + slag stopper is adopted.
[0038] 2. LF refining, refining power is turned on to increase temperature, the outlet temperature is controlled at 1665℃, the composition of molten steel is [C] 0.046%, [Mn] 0.045%, [P] 0.012%, [S] 0.019%, [Ti] 0.0010%, [O] 0.077%.
[0039] 3. RH decarburization and deoxidation, temperature measurement and oxygen determination after RH arrives at the station. The temperature of molten steel is 1655℃, and the oxygen content of molten steel is 0.075%; it is circulated under a vacuum of 120Pa, and argon is used as the lifting gas with a flow rate of 120Nm 3 / h, and after 5 minutes of circulation, the sample was taken, and the composition of the molten steel was [C] 0.001%, [Mn] 0.044%, [P] 0.012%, [S] 0.019%, [Ti] 0.0010%, [O] 0.031%; at this time, 460kg of low-titanium and low-aluminum ferrosilicon and 420kg of lime were added, and the composition of low-titanium and low-aluminum ferrosilicon was [Si] 76%, [Al] 0.02%, [Ti] 0. 01%, [P] 0.015%, [S] 0.010%, and the rest is iron; after circulating for 5 minutes, the sample is taken, and the composition of the molten steel is [C] 0.001%, [Si] 0.22%, [Mn] 0.044%, [P] 0.012%, [S] 0.003%, [Ti] 0.0010%, [Al] 0.0015%, [O] 0.0014%; the slag basicity is 4.0. After deoxidation, continue to circulate for 8 minutes before ending the vacuum, and add low-carbon ladle covering agent (carbon content ≤ 2%) on the surface of the molten steel.
[0040] 4. Continuous casting: The continuous casting process uses a 160mm×160mm cross-section for production. The continuous casting tundish uses an integral smear plug rod tundish, which is baked to 1130°C. This furnace is a continuous casting furnace, the superheat is controlled at 32°C, and the pulling speed is controlled at 2.2m / min; the crystallizer adopts electromagnetic stirring and non-sinusoidal vibration mode, the crystallizer electromagnetic stirring current is 150A, and the frequency is 2.5Hz; the crystallizer amplitude is controlled at ±2.5mm, and the frequency is controlled at 130+40Vopm; the secondary cooling adopts gas mist cooling and weak cooling water distribution; the continuous casting process uses a low-carbon tundish covering agent with a carbon content of ≤2% and an ultra-low carbon protective slag with a carbon content of ≤8%.
[0041] The composition of the finished steel is: [C] 0.002%, [Si] 0.22%, [Mn] 0.044%, [P] 0.012%, [S] 0.003%, [Ti] 0.0010%, [Al] 0.0015%, [O] 0.0013%, and the rest is iron.
[0042] Comparative Example 1
[0043] The converter smelting uses ordinary scrap steel recycled from the society. Compared with Example 1, the manganese content of the converter steel does not meet the requirements.
[0044] 1. BOF smelting, using 115t molten iron + 30t ordinary scrap steel as raw materials for smelting, the manganese content of the converter molten iron is 0.28%, the sulfur content is 0.023%, the carbon content of ordinary scrap steel is 0.06%, the manganese content is 0.35%, the phosphorus content is 0.015%, the sulfur content is 0.018%, and the titanium content is 0.002%; the single slag method is used for smelting; the components of the molten steel at the end of converter smelting are [C] 0.05%, [Mn] 0.076%, [P] 0.012%, [S] 0.020%, [Ti] 0.0010%, [O] 0.072%, the basicity of the converter slag at the end is 3.3, the FeO content of the slag is 18.0%, and the end temperature is 1640℃. It can be seen from the above data that the manganese content of the converter steel is 0.076%, which cannot meet the requirement of manganese content ≤ 0.05%.
[0045] Comparative Example 2
[0046] During the RH deoxidation treatment, the silicon content was less than 0.1%, and the slag basicity was greater than 3.0. Compared with Example 2, the deoxidation effect of the molten steel did not meet the requirements.
[0047] 1. BOF smelting, using 105t molten iron + 40t special scrap steel as raw materials for smelting, the manganese content of the converter molten iron is 0.25%, the sulfur content is 0.022%, the carbon content of the special scrap steel is 0.08%, the manganese content is 0.045%, the phosphorus content is 0.018%, the sulfur content is 0.020%, and the titanium content is 0.002%; the single slag method is used for smelting; the components of the molten steel at the end of converter smelting are [C] 0.041%, [Mn] 0.048%, [P] 0.010%, [S] 0.021%, [Ti] 0.0010%, [O] 0.087%, the basicity of the converter slag at the end is 3.5, the FeO content of the slag is 20.6%, and the end temperature is 1635℃. 500kg lime + 200kg fluorite are added during the steel tapping process, and the double-blocking operation of slide plate + slag stopper is adopted.
[0048] 2. LF refining, refining power is turned on to increase temperature, the outlet temperature is controlled at 1670℃, the molten steel composition is [C] 0.039%, [Mn] 0.047%, [P] 0.010%, [S] 0.021%, [Ti] 0.0010%, [O] 0.085%.
[0049] 3. RH decarburization and deoxidation, temperature measurement and oxygen determination after RH arrives at the station. The temperature of molten steel is 1660℃, and the oxygen content of molten steel is 0.083%; it is circulated under a vacuum of 200Pa, and argon is used as the lifting gas with a flow rate of 120Nm 3 / h, and after circulating for 5 minutes, the sample was taken, and the composition of the molten steel was [C] 0.001%, [Mn] 0.045%, [P] 0.010%, [S] 0.021%, [Ti] 0.0010%, and [O] 0.036%. At this time, 180kg of low-titanium and low-aluminum ferrosilicon and 450kg of lime were added, and the composition of low-titanium and low-aluminum ferrosilicon was [Si] 76%, [Al] 0.02%, [Ti] 0. .01%, [P] 0.015%, [S] 0.010%, and the rest is iron; after circulating for 5 minutes, the sample was taken, and the composition of the molten steel was [C] 0.001%, [Si] 0.05%, [Mn] 0.043%, [P] 0.012%, [S] 0.008%, [Ti] 0.0010%, [Al] 0.002%, [O] 0.0068%; the slag basicity was 4.2. After deoxidation treatment, the oxygen content in the molten steel was 0.0068%, which did not meet the requirement of [O] ≤ 0.005%, and the deoxidation effect did not meet the requirements.
[0050] Comparative Example 3
[0051] The silicon content in the RH deoxidation process is 0.15% to 0.30%, and the slag basicity is less than 3.0. Compared with Example 2, the deoxidation effect of the molten steel does not meet the requirements, and the sulfur content of the molten steel after deoxidation also does not meet the requirements.
[0052] 1. BOF smelting, using 105t molten iron + 40t special scrap steel as raw materials for smelting, the manganese content of the converter molten iron is 0.25%, the sulfur content is 0.022%, the carbon content of the special scrap steel is 0.08%, the manganese content is 0.045%, the phosphorus content is 0.018%, the sulfur content is 0.020%, and the titanium content is 0.002%; the single slag method is used for smelting; the components of the molten steel at the end of converter smelting are [C] 0.041%, [Mn] 0.049%, [P] 0.011%, [S] 0.020%, [Ti] 0.0010%, [O] 0.088%, the basicity of the converter slag at the end is 3.5, the FeO content of the slag is 20.6%, and the end temperature is 1635℃. 500kg lime + 200kg fluorite are added during the steel tapping process, and the double-blocking operation of slide plate + slag stopper is adopted.
[0053] 2. LF refining, refining power is turned on to increase temperature, the outlet temperature is controlled at 1670℃, the molten steel composition is [C] 0.040%, [Mn] 0.048%, [P] 0.011%, [S] 0.020%, [Ti] 0.0010%, [O] 0.086%.
[0054] 3. RH decarburization and deoxidation, temperature measurement and oxygen determination after RH arrives at the station. The temperature of molten steel is 1660℃, and the oxygen content of molten steel is 0.086%; it is circulated under a vacuum of 200Pa, and argon is used as the lifting gas with a flow rate of 120Nm 3 / h, and after circulating for 5 minutes, the sample was taken, and the composition of the molten steel was [C] 0.001%, [Mn] 0.047%, [P] 0.011%, [S] 0.020%, [Ti] 0.0010%, and [O] 0.036%. At this time, 590kg of low-titanium and low-aluminum ferrosilicon and 160kg of lime were added, and the composition of low-titanium and low-aluminum ferrosilicon was [Si] 76%, [Al] 0.02%, [Ti] 0.036%. .01%, [P] 0.015%, [S] 0.010%, and the rest is iron; after 5 minutes of circulation, the sample was taken, and the composition of the molten steel was [C] 0.001%, [Si] 0.25%, [Mn] 0.047%, [P] 0.012%, [S] 0.015%, [Ti] 0.0010%, [Al] 0.002%, [O] 0.0086%; the slag basicity was 1.2. After deoxidation treatment, the sulfur content in the molten steel was 0.015%, and the oxygen content was 0.0086%, both of which did not meet the process requirements of [S] ≤ 0.010% and [O] ≤ 0.005%.
[0055] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing non-aluminum deoxidized industrial pure iron, characterized in that: The process flow of the preparation method is: BOF smelting → LF refining → RH decarburization and deoxidation → continuous casting. The specific steps and process parameters are as follows: Step 1: BOF smelting: the converter smelting adopts the smelting method of molten iron + special scrap steel, the molten iron ratio is controlled at 70%~80%, the special scrap steel ratio is controlled at 20%~30%, and the single slag method is adopted; the terminal temperature is controlled at 1620~1650℃, and the terminal composition is controlled at [C]≤0.05%, [Mn]≤0.05%, [P]≤0.015%, [S]≤0.025%, [Ti]≤0.002%; no deoxidizer and alloy are added during the steel-making process, only lime and fluorite are added, and the double-gear operation of slide plate + slag stopper is adopted; the special scrap steel is the slag steel recovered from the converter smelting of low-sulfur steel grades; Step 2, LF refining, after the molten steel reaches the refining, it is powered on to increase the temperature, and after the refining treatment, the temperature of the molten steel is controlled at 1640-1670°C, and the composition of the molten steel is [C]≤0.05%, [Mn]≤0.05%, [P]≤0.015%, [S]≤0.025%, [O]0.04-0.09%; Step 3: RH decarburization and deoxidation. The RH arrival temperature is controlled at 1630-1660°C. After the molten steel reaches the RH, it is subjected to cyclic decarburization treatment. Argon is used as the lifting gas. The vacuum degree is controlled at 67-1000Pa. After decarburization treatment, the carbon content of the molten steel is ≤0.002%, and the oxygen content of the molten steel is 0.02%-0.06%. Then, low-titanium, low-aluminum ferrosilicon and lime are added for deoxidation treatment. After breaking the air, a low-carbon ladle covering agent with a carbon content of ≤2% is added. Step 4: continuous casting. The continuous casting process uses 160mm×160mm cross-section production. The continuous casting tundish adopts an integral smear plug rod tundish. The tundish is baked to 1050~1150℃, the superheat of the first furnace is controlled at 40~50℃, the superheat of the continuous casting furnace is controlled at 25~35℃, and the pulling speed is controlled at 2.1~2.5m / min; the crystallizer adopts electromagnetic stirring and non-sinusoidal vibration mode; the secondary cooling adopts gas mist cooling and weak cooling water distribution; the continuous casting process uses a low-carbon tundish covering agent with a carbon content of ≤2% and an ultra-low carbon protective slag with a carbon content of ≤8%.
2. The method for preparing non-aluminum deoxidized industrial pure iron according to claim 1, characterized in that: In the single slag smelting described in step 1, the manganese content in the molten iron is ≤0.30%, and the sulfur content is ≤0.03%. The special scrap steel used is slag steel recovered from low-sulfur steel converter smelting, and its composition is [C]≤0.15%, [Mn]≤0.10%, [P]≤0.04%, [S]≤0.025%, and [Ti]≤0.005%.
3. The method for preparing non-aluminum deoxidized industrial pure iron according to claim 1, characterized in that: In step 1, the oxygen content of the final molten steel in the converter is controlled at 0.05%-0.10%, the final slag basicity is controlled at 3.0-3.5, and the slag FeO is controlled at 15%-25%.
4. The method for preparing non-aluminum deoxidized industrial pure iron according to claim 1, characterized in that: In step 1, the amount of lime added is 3-6 kg / t, and the amount of fluorite added is 1-3 kg / t.
5. The method for preparing non-aluminum deoxidized industrial pure iron according to claim 1, characterized in that: The argon flow rate of the cyclic decarburization in step 3 is 100~150Nm 3 / h, and the cycle time is controlled at 3~8min.
6. The method for preparing non-aluminum deoxidized industrial pure iron according to claim 1, characterized in that: In the deoxidation treatment of step 3, the amount of low-titanium and low-aluminum ferrosilicon added is 3.0~6.5kg / t, the amount of lime added is 2.5~4.5kg / t, and the silicon content of the molten steel after deoxidation is controlled at 0.15%~0.45%, the sulfur content is controlled at ≤0.01%, and the slag basicity is >3.
0.
7. The method for preparing non-aluminum deoxidized industrial pure iron according to claim 1, characterized in that: The composition of the low-titanium and low-aluminum ferrosilicon in step 3 is [Si] 70-80%, [Al] ≤ 0.03%, [Ti] ≤ 0.02%, [P] ≤ 0.02%, [S] ≤ 0.010%, and the rest is iron.
8. The method for preparing non-aluminum deoxidized industrial pure iron according to claim 1, characterized in that: After the deoxidation treatment in step 3, the oxygen content of the molten steel is ≤0.002%.
9. The method for preparing non-aluminum deoxidized industrial pure iron according to claim 1, characterized in that: In step 4, the electromagnetic stirring current of the crystallizer is 120~180A, and the frequency is 2.2~2.8Hz; the amplitude of the crystallizer is controlled at -2.5~2.5mm.
Citation Information
Patent Citations
Preparation method of super-pure industrial iron
CN105886690A
Production method of armco iron for amorphous soft magnetic materials
CN106350631A